ANALYSIS OF IMPLEMENTATION OF THE IPARD II PROGRAM IN SERBIA - Radović, Gordana; Subić, Jonel; Pejanović, Vladimir (Economics of Agriculture, 2024)
In Serbia, high expectations were focused on the IPARD Program, considering that in the entire transition period, there was a greater demand for favorable sources of financing for agriculture and rural development compared to their supply. The purpose of the paper is to analyze the implementation of the IPARD II program in Serbia, in the current period, that is, ending with the end of February 2024. The paper uses the following methods: desk research, method of descriptive statistics, as well as methods of analysis and synthesis. The authors conclude that there was a significant utilization of funds from the IPARD II Program in Serbia, ending on February 29, 2024, but also that less than half of the submitted projects met the set criteria. In order for this method of financing to have the best possible effect in Serbia, better education of the inhabitants of rural areas is needed for writing projects. Also, greater financial resources from the European Union are needed in future support programs.